Microstrip lines and slotlines - Garg, Ramesh; Bahl, I. J.; Bozzi, Maurizlo (Artech House, 2013)
Over the years planar transmission line technology has progressed considerably due to developments in ultrawideband (UWB) communications, imaging, and RFID applications. This book covers the development of governing equations, basis functions, Green's function and typical results.